2000
DOI: 10.1177/102986490000400102
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Musical Analysis: Segmentation and Perception of Tension

Abstract: Recent investigations have studied the processes of segmentation and perception of the points of tension which occur while listening to tonal and post tonal music. The present study aims to investigate the criteria people use to segment and memorise post tonal pieces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
2
7
0
1
Order By: Relevance
“…Perceived contrasts, discontinuities, changes, and repetitions at multiple hierarchical levels commonly serve as heuristics that guide the identification of musical segment boundaries (Addessi & Caterina, 2000). Studies in automatic segmentation often refer to these musical novelty points simply as instants of significant change (Foote, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived contrasts, discontinuities, changes, and repetitions at multiple hierarchical levels commonly serve as heuristics that guide the identification of musical segment boundaries (Addessi & Caterina, 2000). Studies in automatic segmentation often refer to these musical novelty points simply as instants of significant change (Foote, 2000).…”
mentioning
confidence: 99%
“…Besides boundary indication time points, analyzed segmentation data in these studies include verbal justifications of segment boundaries, judged time positions, and duration of segments. In particular, boundary indications have been defined according to perceived tension (Addessi & Caterina, 2000;Krumhansl, 1996), expectations and closure (Peebles, 2011), descriptors (Bailes & Dean, 2007;Krumhansl, 1996), and grouping rules (Clarke & Krumhansl, 1990;Deliège, 1987;Frankland & Cohen, 2004;Temperley, 2001). Automatic segmentation systems have been implemented in corpus-based studies; these systems were based on musical features (Hargreaves, Klapuri, & Sandler, 2012;Sanden, Befus, & Zhang, 2012;Smith, Chuan, & Chew, 2013), sets of rules (Bruderer, 2008;Cambouropoulos, 2006;Lartillot & Ayari, 2009;Lartillot, Yazıcı, & Mungan, 2013), or probabilistic methods (Ferrand, Nelson, & Wiggins, 2003;Lattner, Grachten, Agres, & Chacón, 2015;Pearce, Müllensiefen, & Wiggins, 2010), and generally compared against ground-truth data (cf.…”
mentioning
confidence: 99%
“…We observed that the perception of “prominent features” allowed the listeners to perceive several points of segmentations, to divide the piece into the main sections and consequently, to memorize the overall structure of the musical piece. It was also found that there was a correlation between the memorization of the overall structure and the perception of tension and relaxation (Addessi and Caterina, 2000). We listed several musical categories trying to describe the musical features of the perceived “cues”: variation in intensity, timbre variation, acceleration/deceleration or change in rhythm, thickening or thinning of the sound, introduction, repetition, elements concluding or suspending, and pause.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of young and inexperienced listeners at first parse melody by rhythm and only then by pitch contour and mode ( Halpern et al, 1998 ). Tempo/rhythm descriptors are much more prevalent in listeners’ judgments of thematic similarity than of pitch contour ( Addessi and Caterina, 2000 ; McAdams, 2004 ).…”
mentioning
confidence: 99%